Microvessels of bulbar conjunctiva in UPTAH goats - Dobsák, P; Vaskuo, J; Baba, A; Isoyama, T; Saito, I; Siegelová, J; Jancík, J; Svacinová, H; Imachi, K (Artificial organs, 2003)
Aiming to observe directly the microcirculation after total artificial heart (TAH) implantation, we performed a long-term follow-up in 2 goats using conjunctival angioscopy. A short segment of parallel arteriole and venule was photographed and analyzed on computer picture program (magnification 40x). Three main parameters were measured: arteriole diameter, venule diameter, and arteriovenous ratio (A/V ratio). The intrathoracically implanted TAH was the undulation pump total artificial heart (UPTAH) with cardiac output of 100 ml/kg/min. To stabilize the peripheral hemodynamics a 1/R biofeedback control system was used. Our results provided only elementary data about morphology of bulbar microvessels. The main finding was the tendency to general vasoconstriction, more intensive on the venous side (*P < 0.05 in one goat). We did not observe any pathological shapes (e.g., tortuosities, varicosities, or sludge); this result could be attributed to the high effectivity of 1/R control method. These preliminary results should be considered only as an attempt to apply the widely used clinical method of conjunctival angioscopy to the conditions of TAH.
Keywords: Arterioles; Disease Models, Animal; Prosthesis Implantation; arterioly; Postoperative Complications; modely nemocí na zvířatech; kozy; časové faktory; venuly; hemodynamika; vazokonstrikce; Vasoconstriction; konjunktiva; Animals; Goats; mikroskopická angioskopie; implantace protézy; umělé srdce; zvířata; Time Factors; Heart, Artificial; následné studie; Microscopic Angioscopy; mikrocirkulace; Hemodynamics; Microcirculation; pooperační komplikace; Follow-Up Studies; Venules; Conjunctiva